ANALYSIS OF FIBER CONTENT IN BISCUITS, CEREAL BARS, BREAD AND CEREAL - Martins Bock, Francini; Conde, Simara Rufatto (Revista Uningá, 2020)
Food fibers can help preventing intestinal diseases, treating obesity and in the reduction of cardiovascular diseases cases. Because of the benefits of fibers, products that are fiber sources have been created, such as bread, cereal, biscuits and cereal bars. According to the Agency Nacional de Vigilance Sanitary (ANVISA), through the Resolution of the Collegiate Board (RDC) nº 54, from 12 of November, 2012, for a food item be considered a fiber source, it has to contain in its composition 2,5 grams per serving or 3 grams of fibers in 100 ml / 100 g of liquid or solid food. The objective of this study was to analyze and compare the fiber quantities trough the label of these four products that are fiber sources. It was a transversal quantitative study in which were analyzed seven samples of different brands of biscuits, seven of cereal bars, seven of bread and seven of cereals that had their label describing them as fiber sources, 28 products in total. The fiber content described in the label of each product was analyzed and compared with the RDC nº 54 from 2012. The collected data were organized in Microsoft Office Excel sheets. From the 28 product labels, 93% (n=26) were in agreement with the resolution and 7% (n=2) were not of the cereal bar category, not being able to be labeled as fiber sources. It can be concluded that the majority of the products was in agreement with the ANVISA resolution, being able to be labeled as fiber sources.